Evidence in support of hyperkalaemia management strategies: A systematic literature review. Issue 2 (30th January 2018) - Palaka, Eirini; Leonard, Saoirse; Buchanan‐Hughes, Amy; Bobrowska, Anna; Langford, Bryony; Grandy, Susan
Summary: Background: Hyperkalaemia is a potentially life‐threatening condition that can be managed with pharmacological and non‐pharmacological approaches. With the recent development of new hyperkalaemia treatments, new information on safe and effective management of hyperkalaemia has emerged. Objectives: This systematic literature review (SLR) aimed to identify all relevant comparative and non‐comparative clinical data on management of hyperkalaemia in adults. Our secondary aim was to assess the feasibility of quantitatively comparing randomised controlled trial (RCT) data on the novel treatment sodium zirconium cyclosilicate (ZS) and established pharmacological treatments for the non‐emergency management of hyperkalaemia, such as the cation‐exchangers sodium/calcium polystyrene sulphonate (SPS/CPS). Methods: MEDLINE, Embase and the Cochrane Library were searched on 3 rd April 2017, with additional hand‐searches of key congresses and previous SLRs. Articles were screened by two independent reviewers. Eligible records reported interventional or observational studies of pharmacological or non‐pharmacological management of hyperkalaemia in adults. Results: Database searches identified 2, 073 unique records. Two hundred and one publications were included, reporting 30 RCTs, 29 interventional non‐RCTs and 43 observational studies. Interventions investigated in RCTs included ZS (3), SPS/CPS (3), patiromer (4) and combinations of temporising agents (6 RCTs). A robust and meaningful indirect treatment comparison between ZS and long‐established cation‐binding agents (SPS/CPS) was infeasible because of heterogeneity between studies (including time points and dosing) and small sample size in SPS/CPS studies. Conclusions: Despite hyperkalaemia being associated with several chronic diseases, there is a paucity of high‐quality randomised evidence on long‐established treatment options (SPS and CPS) and a limited evidence base for hyperkalaemia management with these agents.